Concentrations of heavy metals in fish species targeted by anglers in central New Jersey: A pilot study. Issue 8 (16th November 2016) - Cambridge, John; Hernandez, Mario; Jensen, Olaf; Buckley, Brian; McCandlish, Elizabeth; Robson, Mark
ABSTRACT: The purpose of this study was to investigate the concentrations of toxic metals in the edible portion of fish tissue obtained from the Raritan River in New Brunswick, New Jersey (NJ) between April and May of 2014. Species collected for this study included commonly caught fish such as bluegill, small and large mouth bass, brown and rainbow trout, bullhead catfish, and white perch. Samples were filleted and the muscle tissue subsequently dehydrated and then chemically digested. Samples were analyzed using Gas chromatography mass spectrometry (GC–MS). Levels of 28 different metals were quantified for each specimen. In general, metal contamination in fish tissues was below the recommended limits. However, lead was found in one sample at a tissue concentration of 88 µg per 225 g fillet, which is above the recommended daily consumption limit as set by the Food and Safety Authority of Ireland. The maximum level found for arsenic was 23 µg per 225 g fillet. The fish samples taken from the Raritan River in New Brunswick, NJ for this study did not contain dangerous levels of most of the metals tested.